KONSEP SERIAL KOMUNIKASI ANTAR BLUETHOOT SEBAGAI MASTER DAN SLAVE UNTUK BERTUKAR INFORMASI DIGITAL - Marcus Gunadi; Lawrence Adi Supriyono (STEKOM PRESS, 2019)
n this digital era and the increasingly developing human resources, it is possible to create new research in this era of development. One example of its development is the discussion of the concept of serial communication. In technology, we know the name of the serial communication. In today's world serial communication is the forerunner of communication between platforms in general. In this journal we will know what serial communication is, it is a communication method that is carried out one way and the concept of sending data is bit by bit or, in other words serial communication is one method of data communication that is sent over a cable which gets one bit of data in a a certain time simultaneously and alternately. In this study using the main tool namely the HC-05 bluethoot module which is used as a master and slave.